Granulocyte-colony stimulating factor in experimental stroke and its effects on infarct size and functional outcome: a systematic review - England, Timothy J.; Gibson, Claire L.; Bath, Philip M.W. (Elsevier, 2009)
Background Granulocyte-colony stimulating factor (G-CSF) shows promise as a treatment for stroke. This systematic review assesses G-CSF in experimental ischaemic stroke.